'Marching at the Speed of the Slowest Man': The Facilitation and Regulation of Student Autonomy in a Pluralist Jewish Day School. Issue 3 (3rd July 2019) - Samson, Maxim G. M.
ABSTRACT: Faith schools are often perceived as restricting students' autonomy through inculcating a single religious ideology and compelling participation in collective worship. Based on interviews and focus groups with parents, students and senior staff, this article investigates how England's one pluralist Jewish secondary school has, in contrast, attempted to accommodate various forms of Jewish practice and facilitate students' agency to determine their Jewish identities as desired. It reveals that students enjoy opportunities to actively negotiate Judaism, but that their autonomy is not without limits, and issues inherent to pluralism exist in executing an ethos accommodative of diverse, personalized expressions of Jewishness.